2022
DOI: 10.1158/1055-9965.epi-21-1449
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Composition and Development of Glucose Intolerance after Allogeneic Hematopoietic Cell Transplantation

Abstract: Background: Allogeneic hematopoietic cell transplantation (HCT) recipients have increased risk of developing glucose intolerance and diabetes mellitus (DM). The strongest risk factor for glucose intolerance is being overweight/obese, as determined by body mass index (BMI), which does not account for differences in body composition. We examined the association between body composition measures from pre-HCT CT and early-onset (≤30 days) de novo glucose intolerance after HCT, and determined its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, in terms of body cell number (BCM), some studies have suggested that the agreement between BCM measurements and DEXA is better in HD patients [ 14 ], but the agreement between BCM measurements and DEXA is poor in renal transplant patients [ 15 ]. Some studies have also suggested that the accuracy of BIA in measuring bone mineral content in HD patients is poor [ 16 ]. The reason for this may be the differences in BIA instruments involved in the studies, and the type and status of patients are also different.…”
Section: Resultsmentioning
confidence: 99%
“…However, in terms of body cell number (BCM), some studies have suggested that the agreement between BCM measurements and DEXA is better in HD patients [ 14 ], but the agreement between BCM measurements and DEXA is poor in renal transplant patients [ 15 ]. Some studies have also suggested that the accuracy of BIA in measuring bone mineral content in HD patients is poor [ 16 ]. The reason for this may be the differences in BIA instruments involved in the studies, and the type and status of patients are also different.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal skeletal muscle was defined as having an abnormally low SMG, because the index represents a composite measure (quantity and quality) of skeletal muscle health, [29][30][31] including in patients undergoing HCT. 25 Individuals were considered to have abnormal visceral adipose tissue (VAT) according to sex-based VAT tertile cutoffs (.100 cm 2 [female]; .168 cm 2 [male]).…”
Section: Body Composition At Car T-cell Therapymentioning
confidence: 99%
“…Recent advances in software technology have facilitated the near real-time integration of body muscle and fat measurements into CT imaging obtained for standard clinical care, setting the stage for risk stratification for primary or secondary prevention. [22][23][24][25] The overall aims of this study were to describe the association between skeletal muscle measurements obtained from pretreatment CT images and postinfusion acute toxicities (eg, CRS, ICANS) as well as 1-year PFS and OS after CAR T-cell therapy, and to identify individuals at highest risk for worse outcomes after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of body cell number (BCM), some studies have suggested that the agreement between BCM measurements and DEXA is better in HD patients [14], but the agreement between BCM measurements and DEXA is poor in renal transplant patients [15]. Some studies have also suggested that the accuracy of BIA in measuring bone mineral content in HD patients is poor, but more studies are needed to comprehensively evaluate [16].…”
Section: Compared With Other Body Composition Measurementmentioning
confidence: 99%